(untitled) (Indonesian Journal of Primatology, 2024)
Leukocytes play a crucial role in immune defense mechanisms. The differential leukocyte count and morphological examination are commonly used in laboratory test to identify anomalies in leukocytes distribution and detect morphological irregularities. This study aimed to performed a differential leukocyte count using peripheral blood smear samples obtained from 5 Cynomolgus monkey (Macaca fascicularis) bloods. Staining of peripheral blood smears was followed by observation under a light microscope to perform differential leukocyte counts and morphological examination. The differential leukocyte count results showed signs of lymphocytosis and neutropenia in samples AJ400, AB924, and AJ150, which may suggest infections, such as viral or bacterial infections. Additionally, signs of monocytosis showed in samples AB924 and AJ150, possibly attributed to bacteremia or endocarditis. However, the morphological examination showed no abnormalities or immature cells.